Ordenamiento y demarcacion territorial como instrumento de planificacion para el desarrollo sostenible de la region Ancash - Cruz Reyes, Fray Masias (2009)
The department of Ancash, like others departments in the country, trough history has been occupied with purposes of settlement and exploitation of its natural resources spontaneously and according to political, social, and economic national and international situation generating as consequences territorial imbalances resulting in favor of coastal strip and Callejon de Huaylas, to expenses the Andean region and the Marañon valley. This is a useful reference to make a geographic-political-administrative and socio-economic population diagnosis which confirms that the political demarcation of many districts and provinces of this department in some cases is indefinite and imprecise, what conditions and make difficult good governance creating territorial problems; where the territorial ordaining used as a planning tool, help to correct these imbalances and promotes integration based on the geographical, historical and socio-economic-cultural conditions of peoples